2019
DOI: 10.3390/ijms20194851
|View full text |Cite
|
Sign up to set email alerts
|

Omega Fatty Acids and Inflammatory Bowel Diseases: An Overview

Abstract: Inflammatory bowel diseases (IBD) are chronic, inflammatory processes that affect the gastrointestinal tract and are mainly represented by ulcerative colitis (UC) and Crohn’s disease (CD). Omega 3 (ω3) fatty acids (eicosapentanoic acid and docosahexaenoic acid) show an indispensable role in the inflammatory processes and, for these reasons, we aimed to review the effects of these acids on UC and CD. Databases such as PUMED and EMBASE were searched, and the final selection included fifteen studies that fulfille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 47 publications
0
43
0
5
Order By: Relevance
“…A plethora of recent studies have highlighted the role of gut dysbiosis in these conditions ( Pittayanon et al, 2020 ). FO and its n-3-PUFAs have been suggested as a potential adjunctive treatment for IBDs, although the clinical data that have been obtained so far come from small cohorts of patients using variable modes of consumption (types of foods or types of formulation) and are therefore still controversial ( Marton et al, 2019 ). On the other hand, while various Cannabis preparations have been tested in IBD patients as a potential treatment, purified cannabinoids have been mostly tested in animal models of colitis ( Couch et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of recent studies have highlighted the role of gut dysbiosis in these conditions ( Pittayanon et al, 2020 ). FO and its n-3-PUFAs have been suggested as a potential adjunctive treatment for IBDs, although the clinical data that have been obtained so far come from small cohorts of patients using variable modes of consumption (types of foods or types of formulation) and are therefore still controversial ( Marton et al, 2019 ). On the other hand, while various Cannabis preparations have been tested in IBD patients as a potential treatment, purified cannabinoids have been mostly tested in animal models of colitis ( Couch et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed for this property of FO, including, but not limited to, the capability of EPA and DHA to: 1) replace arachidonic acid (AA) in membrane phospholipids, and hence reduce the amounts of this omega-6 PUFA that can act as direct or indirect biosynthetic precursors for endocannabinoids and pro-inflammatory eicosanoids ( Calder, 2017 ; Innes and Calder, 2018 ); and 2) affect the gut microbiota to ameliorate gut dysbiosis and counteract, among others, its contribution to chronic, lowgrade inflammation ( Costantini et al, 2017 ). As a consequence, it has been suggested that FO may provide therapeutic relief for IBDs ( Marton et al, 2019 ). Also, plant cannabinoids from Cannabis sativa , and in particular: 1) Δ 9 -tetrahydrocannabinol (THC), which activates cannabinoid receptor of type-1 (CB1) or, particularly, type-2 (CB2) [see ( Ibeas Bih et al, 2015 ; Turner et al, 2017 ) for review], and 2) cannabidiol (CBD), which modulates several pro-inflammatory targets [see ( Burstein, 2015 ) for review] have been shown to produce anti-inflammatory effects in animal models of several inflammatory disorders, including IBDs ( Gotfried et al, 2020 ; Williamson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EPA and DHA, but not ALA, may protect against development of ulcerative colitis. With regard to the treatment of IBD, there have been a number of trials of ω-3 PUFAs (mainly preparations of EPA plus DHA) over the years; trials conducted prior to 2009 are reviewed in [ 84 ] while trials published since 2010 are reviewed in [ 85 ]. The focus of the majority of such human trials has not been on the function of the intestinal barrier and epithelial cells specifically, but rather on macroscopic inflammatory scores, relapse and remission rates, and systemic markers of inflammation such as plasma concentrations of cytokines.…”
Section: ω-3 Pufas and Human Ibdmentioning
confidence: 99%
“…The patient often presents tenesmus, blood in the stool, weight loss, diarrhea, flatulence, and abdominal pain, resulting in a substantial decrease in quality of life. Furthermore, it is related to psychological disorders [23,24].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%